Harmonisasi Syariah, Fatwa, dan HAM Anak untuk Perlindungan dan Akses Pendidikan di Masyarakat Plural - Muchamad Masrur; Gilang Fawwaz Agnan Hermawan (Student Scientific Creativity Journal, 2026)
Education is the basic right of every child that is internationally recognized; However, in practice, it still faces various challenges, especially in a pluralistic society that includes diverse legal and cultural norms. In this context, Islamic law through sharia and fatwas plays an important role in ensuring the protection and access to children's education, and therefore needs to be aligned with international standards of the child's rights. This research aims to analyze how harmonization between sharia, fatwas, and children's human rights can be achieved to create fair and sustainable education, as well as to identify innovative strategies that can be applied in the context of legal pluralism. The method used is normative legal research, using a qualitative approach through doctrinal analysis, official fatwas, and international human rights instruments. The results of the study show that integrating sharia, fatwas, and children's human rights allows for the creation of a legal framework that supports inclusive, equitable, and sustainable education, as well as providing a basis for innovative legal policies that are responsive to societal diversity. These findings are expected to contribute to the development of modern Islamic law that is in line with children's rights.